Mg/ZrO2 Metal Matrix Nanocomposites Fabricated by Friction Stir Processing: Microstructure, Mechanical Properties, and Corrosion Behavior - Qiao, Ke; Zhang, Ting; Wang, Kuaishe; Yuan, Shengnan; Zhang, Shengyi; Wang, Liqiang; Wang, Zhi; Peng, Pai; Cai, Jun; Liu, Chaozong; Wang, Wen (Frontiers in Bioengineering and Biotechnology, 2021)
Magnesium (Mg) and its alloys have attached more and more attention because of their potential as a new type of biodegradable metal materials. In this work, AZ31/ZrO2 nanocomposites with good uniformity were prepared successfully by friction stir processing (FSP). The scanning electron microscope (SEM) and transmission electron microscope (TEM) were used to characterize the microstructure of the composites. The mechanical properties, electrochemical corrosion properties and biological properties were evaluated. In addition, the effect of reinforced particles (ZrO2) on the microstructure and properties of the composite was studied comparing with FSP AZ31 Mg alloy. The results show that compared with the base metal (BM), the AZ31/ZrO2 composite material achieves homogenization, densification, and grain refinement after FSP. The combination of dynamic recrystallization and ZrO2 particles leads to grain refinement of Mg alloy, and the average grain size of AZ31/ZrO2 composites is 3.2 μm. After FSP, the c-axis of grain is deflected under the compression stress of shoulder and the shear stress of pin. The ultimate tensile strength (UTS) and yield strength (YS) of BM were 283 MPa and 137 MPa, respectively, the UTS and YS of AZ31/ZrO2 composites were 427 MPa and 217 MPa, respectively. The grain refinement and Orowan strengthening are the major strengthening mechanisms. Moreover, the corrosion resistance in simulated body fluid of Mg alloy is improved by grain refinement and the barrier effect of ZrO2.